TOWARDS THE IMPLEMENTATION OF COOPERATIVE LEARNING IN INDONESIA: A Case study of a Large, English as Foreign Language Class in a Middle School in Bandung - Mian, Yusuf (2017)
Large-class teaching is inevitable in the majority of nations, specifically in English classes, due to the growing demand for this skill. A number of strategies can be employed to handle a large class successfully. However, in traditional teaching methods, the classes are teacher-centered with an excessive teacher talking time, which usually does not provide the students opportunities to engage actively in the classroom activities. Conversely, cooperative learning (CL), being a learner-centered approach, provides abundant opportunities to acquire target language competence efficiently through active involvement in the class. This study explores the implementation of cooperative group work in a middle school EFL classroom in Indonesia. A case study design is employed to investigate the implementation of CL, it benefits, and the challenges encountered. Classroom observations, questionnaires, interviews, focus group discussions, and institutional documents were used to gather data. The study findings revealed that partial CL was implemented. CL activities were shown to enhance students' engagement in class, and their academic and social skill achievement. In addition, students had fun, in a pleasing learning environment. Challenges, such as the lack of equal involvement of all group members were also encountered. This study confirms that cooperative group work is useful in handling large classes, provided it is based on fundamental the elements of the theory. It is recommended that in-service teachers be trained in order to comprehend the CL approach fully, and to be able to adapt it appropriately for the indigenous context. Effective use of CL will help enhance students' engagement in large EFL classes.